2008
DOI: 10.1007/s10603-008-9067-4
|View full text |Cite
|
Sign up to set email alerts
|

Europeanisation of Product Liability in the Asia-Pacific Region: A Preliminary Empirical Benchmark

Abstract: Product liability, Tort law reform, Asia-Pacific,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…61 The foundations of China's product liability system also seem to echo the findings of a survey of Asia-Pacific countries which found that the European product liability system was the central model for reform, with the US viewed as an outlier. 62 China is thus converging with regional norms in this field, as well as being broadly in line with global trends. Examining product liability norms from a regional perspective also highlights the relative futility of dividing the relevant jurisdictions into civil law and common law 'families'; in the product liability arena, these distinctions are not useful as there is a great deal of consensus around fundamental norms.…”
Section: B Implications For Product Liability Systems Globallymentioning
confidence: 83%
“…61 The foundations of China's product liability system also seem to echo the findings of a survey of Asia-Pacific countries which found that the European product liability system was the central model for reform, with the US viewed as an outlier. 62 China is thus converging with regional norms in this field, as well as being broadly in line with global trends. Examining product liability norms from a regional perspective also highlights the relative futility of dividing the relevant jurisdictions into civil law and common law 'families'; in the product liability arena, these distinctions are not useful as there is a great deal of consensus around fundamental norms.…”
Section: B Implications For Product Liability Systems Globallymentioning
confidence: 83%
“…As part of the broader rule of law, product liability is governed by a number of statutes as well as other general and industryspecific legislation. Depending on the specific industry and circumstances, there may be occasions when two or more laws or rules overlap [7] .…”
Section: B Theories Of Product Liability Lawmentioning
confidence: 99%
“…Footnote4 Econsumer.gov is an international organization comprised of consumer protection authorities from 41 different nations [8,9] . Lottery, sweepstake, and prize scams are commonplace, as are imposters posing as loved ones, government officials, business partners, or romantic interests while trying to get you to send money or provide personal information [7] . In addition to: phones, mobile devices, and phone services anything else, regarding.…”
Section: Developments In India's Product Liability Lawmentioning
confidence: 99%